In vitro activity of Spirulina platensis water extract against different Candida species isolated from vulvo-vaginal candidiasis cases. - Antonella Marangoni; Claudio Foschi; Matteo Micucci; Rogers Alberto Nahui Palomino; Tullia Gallina Toschi; Beatrice Vitali; Luca Camarda; Mara Mandrioli; Marta De Giorgio; Rita Aldini; Ivan Corazza; Alberto Chiarini; et al. (PLoS ONE, 2017)
The high incidence of vulvo-vaginal candidiasis, combined with the growing problems about azole resistance and toxicity of antifungal drugs, highlights the need for the development of new effective strategies for the treatment of this condition. In this context, natural compounds represent promising alternatives. The cyanobacterium Spirulina platensis, a blue-green alga, exhibits antimicrobial activities against several microorganisms. Nevertheless, only few data about the antifungal properties of Spirulina platensis are available and its potential toxic effects have not been largely investigated. The aim of this study was to evaluate the in vitro activity of a fully-characterized water extract of Spirulina platensis against 22 strains of Candida spp. Prior to considering its potential topical use, we both investigated whether the extract exerted target activities on guinea pig uterine smooth muscle, and the impact of Spirulina platensis on the dominant microorganisms of the vaginal microbiota (i.e., lactobacilli), in order to exclude possible adverse events. By means of a broth microdilution assay, we found that the microalga extract possesses good antifungal properties (MIC: 0.125-0.5 mg/ml), against all the Candida species with a fungicidal activity. At the concentrations active against candida, Spirulina platensis did not modify the spontaneous basic waves pattern of uterine myometrium as underlined by the absence of aberrant contractions, and did not affect the main health-promoting bacteria of the vaginal ecosystem. Finally, we evaluated the selectivity index of our extract by testing its cytotoxicity on three different cell lines and it showed values ranging between 2 and 16. Further in vivo studies are needed, in particular to evaluate the use of control-release formulations in order to maintain Spirulina platensis concentrations at anti-Candida active doses but below the toxic levels found in the present work.